2002
DOI: 10.1021/jp0204197
|View full text |Cite
|
Sign up to set email alerts
|

Near Infrared Optical Absorption of Gold Nanoparticle Aggregates

Abstract: The reduction of HAuCl 4 by Na 2 S has been reported to produce gold nanoparticles with an optical absorption in the near-infrared along with its characteristic absorption in the visible. The optical resonances in the visible are due to the gold surface plasma, which are a function of the geometry of the particles. The near-infrared absorption had been attributed to the formation of Au 2 S/Au core/shell structures. In this report we present new electronic absorption, electron microscopy, and X-ray absorption d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
260
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 257 publications
(280 citation statements)
references
References 33 publications
(74 reference statements)
19
260
1
Order By: Relevance
“…Although only a weak absorption near 780 nm is observed, SERS is still demonstrated to work effectively. This suggests that either the nanoparticles/aggregates absorbing at 780 nm are strongly SERS active due to their favorable surface chemistry or that the nanoparticles have further aggregated upon concentrating and drying for the SERS experiment, which may have caused a red-shift of the absorption band and increased absorption at 780 nm similar to what has been observed for gold nanoparticles [19]. The spectrum in Fig.…”
Section: Resultssupporting
confidence: 52%
“…Although only a weak absorption near 780 nm is observed, SERS is still demonstrated to work effectively. This suggests that either the nanoparticles/aggregates absorbing at 780 nm are strongly SERS active due to their favorable surface chemistry or that the nanoparticles have further aggregated upon concentrating and drying for the SERS experiment, which may have caused a red-shift of the absorption band and increased absorption at 780 nm similar to what has been observed for gold nanoparticles [19]. The spectrum in Fig.…”
Section: Resultssupporting
confidence: 52%
“…[62] When Au nanoparticles are near each other in solution, an extended plasmon band can be observed that does not appear for isolated nanoparticles. [60] Proximity-induced plasmon coupling provides the basis for a nanoruler. [61,68] Magnetic coupling between nanoparticles may seem less of a surprise than electronic coupling.…”
Section: Proximity Effects -Impacts Of Separation Aggregation and Smentioning
confidence: 99%
“…Such nanoparticles exhibit different colours due to surface plasmon resonance effects which result from the resonance interaction of incoming electromagnetic radiation in the visible region with the collective plasmon oscillations at the metal surface [1]. This gives rise to intense absorptions in the visible spectrum.…”
Section: Introductionmentioning
confidence: 99%